Uwagi o języku kodeksu cywilnego: [Remarks on the language of the civil code] (Studia Prawnicze / The Legal Studies, 1983)
The authors of the Polish civil code of 1964 tried to use colloquial language which is easily understood by masses of people and, at the same time, precise from the legal point of view. The law is quite detailed and flexible so it deserves a high opinion. In spite of this there are some linguistic incorsistenoies which are being discussed in the present article. It refers to such terms used equivocally as: property, condition, order, delivery. In other cases the terminology is irresolute; it concerns e.g. the definition of money, word "order" in some experessions, etc. In other cases departure from the terminology established in the interwar period has been observed.The author draws a final conclusion that the assistance of linguists is useful only when it is supervised by lawyers.